Effects of early psychosocial deprivation on the development of memory and executive function - Bos, Karen J.; Fox, Nathan; Zeanah, Charles H.; Nelson, Charles A. (Frontiers in Behavioral Neuroscience, 2009)
This study investigated the effects of early institutional care on memory and executive functioning. Subjects were participants in the Bucharest Early Intervention Project (BEIP) and included institutionalized children, children with a history of institutionalization who were assigned to a foster care intervention, and community children in Bucharest, Romania. Memory and executive functioning were assessed at the age of eight years using the Cambridge Neuropsychological Test and Automated Battery (CANTAB). As expected, children with a history of early institutional care performed worse on measures of both visual memory and executive functioning compared to their peers without a history of institutional care. In comparing children randomly assigned to the foster care intervention with their peers who had continued care in the institution, initial comparisons did not show significant differences on any of the memory or executive functioning outcomes. However, for one of the measures of executive functioning, after controlling for birth weight, head circumference, and duration of time spent in early institutional care, the foster care intervention was a significant predictor of scores. These results support and extend previous findings of deficits in memory and executive functioning among school-age children with a history of early deprivation due to institutional care. This study has implications for the millions of children who continue to experience the psychosocial deprivation associated with early institutional care.